2009
DOI: 10.1038/hr.2009.99
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of osteoporosis by angiotensin-converting enzyme inhibitor in spontaneous hypertensive rats

Abstract: A recent analysis of clinical studies suggests that angiotensin-converting enzyme (ACE) inhibitors might reduce bone fractures. In this study, we examined whether an ACE inhibitor might attenuate osteoporosis in a hypertensive rat model. In spontaneous hypertensive rats (SHRs), estrogen deficiency induced by ovariectomy (OVX) resulted in a significant increase in osteoclast activation as assessed by the tartrate-resistant acid phosphatase (TRAP) activity in the tibia, accompanied by a significant decrease in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
38
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 25 publications
6
38
0
Order By: Relevance
“…Such inhibition is partly explained by cilnidipine's sympatholytic action mediated by the N-type calcium channel blockade with a reduction in renin secretion by juxtaglomerular cells through renal sympathetic innervation. Because the inhibition of renin-angiotensin system with angiotensin receptor blockers and angiotensin-converting enzyme inhibitors in experimental models prevented osteoporosis in ovariectomy-induced bone loss, 22,34,35 both the inhibition of renin-angiotensin system and the adrenergic stimulation by cilnidipine might have cumulative benefits on bone metabolism.…”
Section: Cilnidipine and Osteoporosis Hideo Shimizu Et Almentioning
confidence: 99%
“…Such inhibition is partly explained by cilnidipine's sympatholytic action mediated by the N-type calcium channel blockade with a reduction in renin secretion by juxtaglomerular cells through renal sympathetic innervation. Because the inhibition of renin-angiotensin system with angiotensin receptor blockers and angiotensin-converting enzyme inhibitors in experimental models prevented osteoporosis in ovariectomy-induced bone loss, 22,34,35 both the inhibition of renin-angiotensin system and the adrenergic stimulation by cilnidipine might have cumulative benefits on bone metabolism.…”
Section: Cilnidipine and Osteoporosis Hideo Shimizu Et Almentioning
confidence: 99%
“…Bone density measurements were performed by dual-energy x-ray absorptiometry (GE-Lunar DPX-IQ; Madison, Wis) and microcomputed tomography (x-ray computed tomography system, SMX-100CT-SV; Shimazu, Osaka, Japan) and software TRI/3D-BON (RATOC System Engineering Co Ltd, Tokyo, Japan) as described previously. 23 …”
Section: Microcomputed Tomographymentioning
confidence: 99%
“…2,6,7,9) Epidemiological studies have reported the benefit of such antihypertensive drugs as ACE inhibitors and angiotensin II receptor blockers (ARB) for increasing the bone mass and decreasing the risk of bone fractures. 10,11) We therefore hypothesized that bone RAS might be a local regulating system for bone metabolism.…”
Section: Involvement Of the Skeletal Renin-angiotensin System In Age-mentioning
confidence: 99%